Methods of bremsstrahlung monitoring for photonuclear technologies - Karasyov, S.P.; Nikiforov, V.I.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N. (Вопросы атомной науки и техники, 2006)
The paper describes the methods and devices proposed for measuring the main parameters of high-power highenergy
bremsstrahlung sources. It has been suggested that space-energy characteristics of radiation should be investigated
by the method of combined (γ, n) activation of a set of foils that have different energy thresholds of the reaction.
In each energy range, the geometrical characteristics of the radiation field are reconstructed from the foil surface
activity distributions. The last ones are determined through one-dimensional scanning of the foils by a specially
designed detecting head that includes a linear matrix from collimated CdZnTe-base detectors. For a continuous
monitoring of the bremsstrahlung power flow it is suggested that the method of feed-free secondary emission should
be used, with a plane-parallel detector having two plates of different thickness as the base. A preliminary analysis of
the geometry and applicability conditions of each of the detector systems was performed by the method of computer
simulation based on the PENELOPE software system Описаны предложенные авторами методы и средства измерения основных параметров мощных источников высокоэнергетичного тормозного излучения. Исследование пространственно-энергетических характеристик излучения предлагается выполнять методом совместного (γ,n)-активирования набора фольг из материалов, имеющих различный энергетический порог реакции. Геометрические характеристики поля излучения в каждом энергетическом диапазоне восстанавливают из распределений поверхностной активности фольг. Последние определяются путем одномерного сканирования фольг специально разработанной детекторной головкой, включающей линейную матрицу из коллимированных детекторов на основе CdZnTe. Для непрерывного мониторинга потока мощности тормозного излучения предложено использовать метод вторичной эмиссии без питания на основе плоскопараллельного детектора из двух пластин с различной толщиной. Предварительный анализ геометрии и условий применения каждой из детекторных систем выполнен методом компьютерного моделирования на основе программной системы PENELOPE/2001. Описані запропоновані авторами методи і засоби вимірювання основних параметрів потужних джерел
високоенергетичного гальмівного випромінювання. Дослідження просторово-енергетичних характеристик
випромінювання пропонується виконувати методом спільного (γ,n) - активування набору фольг з матеріалів,
що мають різний енергетичний поріг реакції. Геометричні характеристики поля випромінювання в кожному
енергетичному діапазоні визначають з розподілів поверхневої активності фольг. Останні визначаються
шляхом одномірного сканування фольг спеціально розробленою детекторною голівкою, що включає лінійну
матрицю з колімованих детекторів на основі CdZnTe. Для безперервного моніторингу потоку потужності
гальмівного випромінювання запропоновано використовувати метод вторинної емісії без живлення на
основі плоскопаралельного детектора з двох пластин з різною товщиною. Попередній аналіз геометрії і умов
застосування кожної з детекторних систем виконаний методом комп'ютерного моделювання на основі
програмної системи PENELOPE/2001.